Determination of nonlinear refractive index of paprika oil and pepper oil under cw visible laser illumination - I.T.Abed-Ali; C.A.Emshary (University of Thi-Qar Journal, 2019)
We report the observation of multiple diffraction rings patterns in paprika and pepper oils using continuous wave laser beams .The patterns occur at relatively low intensities . The number of rings together with outermost ring diameter of each pattern increases monotonically with increasing input power . The total changes in refractive index , ?n ,and nonlinear refractive index,n2 ,are determined using the number of rings observed in both samples and 473 nm and 532 nm laser beams . We obtained good values of ?n = 0.01 and n2 = 10-6 cm2/w . These large values are attributed to thermal effects .